An evaluation of five regional health information technology-based programmes to improve health and social care coordination: A quasi-experimental controlled before/after mixed design. Issue 2 (April 2022) - Salmi, Louis-Rachid; Roberts, Tamara; Renaud, Thomas; Buffeteau, Sophie; Cueille, Sandrine; Fourneyron, Emmanuelle; Gaillard, Aurélie; Abraham, Maelys; Arditi, Nora; Castry, Mathieu; Daniel, Fabien; N'gom, N'deye Fatou; et al.
Objectives: Health information technology (HIT) can help coordinate health and social actors involved in patients' pathways. We assess five regional HIT-based programmes (' Territoires de Soins Numériques ' or TSN) introduced in France, covering the period 2012–2018. Methods: This was a quasi-experimental controlled before/after mixed design. We used data from the French National Health Insurance database, qualitative and quantitative surveys, and information extracted from project documents and databases. We assessed the impact of TSN using four main impact indicators: emergency room visits, unplanned hospitalizations, avoidable hospitalizations and rehospitalization within 30 days. We also collected qualitative and secondary quantitative data covering perceived needs, knowledge, use, satisfaction, adoption and understanding of projects, pathway experience, impact on professional practices and appropriateness of hospitalizations. Results: TSN implemented a heterogeneous mix of HIT. Implementation was slower than expected and was not well documented. Users perceived the HIT as having a positive but weak overall effect. There were no significant differences in trends for the main impact indicators, nor on the appropriateness of hospitalizations, but favourable trends on secondary polypharmacy indicators. Conclusions: If similar innovations take place in future, they should be based on a logical framework that defines causal, measurable links between services provided and expected impacts.